Analisis Kesiapan Wisata Medis (Medical Tourism) Rumah Sakit Awal Bros Batam Kepulauan Riau - Ronny Sutanto; Hilda Muliana; Sabda Wahab (LPPM Universitas Respati Indonesia, 2022)
Global competition on medical industry has lead patients from developed country to travel to non developed country to seek medication for the even high quality and affordable price reason. Government of Indonesia has announced the new Policy for medical tourism “Permenkes no 76 year 2015” as final official law statement. This qualitative study aimed as recommendation for analysis of readiness of the 3 components consists of Awal Bros Hospital Batam, Government of Batam, and Batam Travel Agency. Using the methods of case study conducted on November – December 2016. Research through on in depth‐interview, collecting scondary data, and observation. Using a non structured interview instrument guideline dan triangulaiton method overview of the assessment obtained are Awal Bros hospital, Government of Batam, and Batam Travel Agency are in posistion ready to prepare for medical tourism service in Batam. Recommendation are made for the Government of Batam adding Blueprint of the 10th culture promotion for medical tourism including tax incentif for health indsutry in Batam, Draft Cooperation between Batam Travel Agency with Government of Batam dan Awal Bros Hospital Batam is encouraged, also enhancing Collaborative strategy for Awal Bros Batam Hospital with its Foreign hospital affiliation.